Deciding Elections in Africa: Comparative Role of the Courts and the Ballot Box in Nigeria and Kenya - Genyi, Akwaya George; Ortom, Eunice (Advances in Social Sciences Research Journal, 2017)
Democratic sustenance is critical to democratic stability and the conduct of free, fair and credible elections is logically instrumental to institutionalizing the democratic culture in Africa. Post election peace is an obvious sign of this libertarian competitive process to power. There are signs of resilient progress along this continuum in Africa and a necessary facilitator of this process is the court system because democratic elections represent a contest that its outcome could be subject to legal challenges. This paper argues that shifting to the courts to decide election outcomes is not to substitute the ballot box with the judiciary as the principal mechanism for conferring victory but to underscore the relevance of the rule of law in the institutional process of post-election peace building. Contemporary electoral experiences in Kenya and Nigeria offer useful insights into the role of the courts in affirming democratic principles and mechanisms for entrenching democratic peace through merit based judicial outcomes rather than the resort to technicalities that seek to uphold ‘injustice’ rather than the triumph of the ballot choice already established through the sanctity of elections. Electoral laws of evidence should be amended to shift the burden of proof to the respondent so that substantive justice can be achieved rather than seeking refuge in technicalities that should not be the prime issues in dispute. Key words: democratic peace, elections, judiciary